Follicular carcinoma of the thyroid following radioactive iodine treatment for Graves' disease. - Staffurth, J. S. (BMJ Group, 1988)
A 67 year old man presented with a well differentiated follicular carcinoma of the thyroid 17 years after he had been given radioactive iodine for Graves' disease. As this was insufficient to cure him he had continued to take propylthiouracil regularly. The tumour, which had completely replaced the thyroid, was apparently maintaining thyrotoxicosis. The implications of this management are discussed and it is concluded that antithyroid drugs should not be given on a long term basis after therapeutic radioiodine has been administered.